Post‐thrombotic syndrome in children: Measurement properties of CAPTSure, a new diagnostic tool. Issue 4 (28th August 2019) - Avila, Maria Laura; Feldman, Brian M.; Pullenayegum, Eleanor; Lumia, Celeste; Montoya, Madeline I.; Vincelli, Jennifer; Williams, Suzan; Brandão, Leonardo R.
Abstract: Background: CAPTsure (Clinical Assessment of PTS) is a new tool for diagnosis and severity rating of pediatric postthrombotic syndrome (PTS). Our objective was to test the reliability, measurement error, and minimal detectable change of CAPTSure. Methods: Children aged newborn to 18 years who sustained upper extremity or lower extremity deep vein thrombosis (DVT) were enrolled ≥ 6 months after DVT diagnosis. Patients were assessed by 2 raters to determine the reliability of the clinician assessment component (CC) of CAPTSure. Patients/proxies completed CAPTSure at baseline and approximately 2 weeks later to assess test‐retest reliability of the symptoms component (SC). Results: Of 148 patients enrolled in the study; 30 had sustained either bilateral or both upper and lower extremity DVT. Hence, 178 extremities were assessed for PTS signs (86 upper extremity, 92 lower extremity). Intraclass correlation coefficient (ICC) for the CC was 0.89 (95% confidence interval [CI], 0.84‐0.93) for upper extremity and 0.88 (95% CI, 0.83‐0.92) for lower extremity. Nonclinicians performed 59% of measurements. Ninety‐eight patients completed the SC at baseline and follow‐up, for a total of 60 upper extremity and 61 lower extremity assessments. ICC for the SC was 0.89 (95% CI, 0.84‐0.93) for upper extremity and 0.92 (0.87‐0.95) for lower extremity. ICC for CAPTSure was 0.92 (95% CI, 0.87‐0.95) for upper extremity and 0.93 (95% CI, 0.88‐0.95) for lower extremity assessment. Measurement error ranged between 1.7 and 4.3 of 100 points. A change of approximately 11 of 100 points in CAPTSure score would be required to be confident that there was a change in PTS severity. Conclusion: CAPTSure has excellent reliability and a small measurement error, even when applied by nonhematologists.